(untitled) (International Journal of Engineering and Computer Science, 2015)
Liver cancer is a chronic cancer which originates in the liver. The tumor may be originated elsewhere in the body but latter it migrates towards the liver and makes severe damage to it. In many cases it could not be possible to identify the intensity but symptomatically abdominal pain, jaundice, dysfunction of liver will lead to found its presence. Many of the signs and symptoms of liver cancer can also be caused by other conditions like High blood calcium levels (hypocalcaemia), Low blood sugar levels (hypoglycaemia), Breast enlargement (gynecomastia), High counts of red blood cells (erythrocytosis), High cholesterol levels. Treatment of any cancer mainly depends on tumor size and grading. Hepatocellular carcinoma is the most common type of liver cancer. The best method of diagnosis involves CT scan of abdomen, it provides accurate results. This proposed method includes segmentation and K-means clustering for segmenting the computed tomography (CT) images, and probabilistic neural network is used to detect the tumor in the earlier stages.